2020
DOI: 10.1111/jvh.13424
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hepatitis E virus infection across England and Wales 2009‐2017: Demography, virology and outcomes

Abstract: The first clinical case of persistent HEV infection in England was reported in 2009. We describe the demography, virology and outcomes of patients identified with persistent HEV infection in England and Wales between 2009 and 2017. A series of 94 patients with persistent HEV infection, defined by HEV viraemia of more than 12 weeks, was identified through routine reference laboratory testing. Virology, serology and clinical data were recorded through an approved PHE Enhanced Surveillance System. Sixty-six | 421… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
(72 reference statements)
1
15
0
Order By: Relevance
“…A series of 94 patients with persistent HEV infection (viraemia of more than 12 weeks) from England and Wales showed that all patients were immunocompromised: 70.2% were transplant recipients, 17% had an underlying haematological malignancy and 6% had advanced HIV infection. Seventeen per cent of the 65 patients treated by ribavirin, had a virological relapse 30 …”
Section: Chronic Hepatitismentioning
confidence: 99%
See 3 more Smart Citations
“…A series of 94 patients with persistent HEV infection (viraemia of more than 12 weeks) from England and Wales showed that all patients were immunocompromised: 70.2% were transplant recipients, 17% had an underlying haematological malignancy and 6% had advanced HIV infection. Seventeen per cent of the 65 patients treated by ribavirin, had a virological relapse 30 …”
Section: Chronic Hepatitismentioning
confidence: 99%
“…These patients may experience viral clearance over time and the return of immunity. This may induce a rebound in cytolysis and severe acute hepatitis 30 …”
Section: Chronic Hepatitismentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore worthwhile to emphasize the reason for and the way in which these patients are immunosuppressed in order to learn more about the mechanisms involved. A recent study by Ankcorn et al [ 138 ] investigated patients suffering from persistent HEV infection over a long period of time for underlying disorders. A history of SOT was present in approximately 60% of the patients.…”
Section: Clinical Link Between Lymphoid Cell Impairment and Hev Outcomementioning
confidence: 99%